Tu príncipe azul es un agresor: la idealización del amor romántico y su influencia en la violencia de género dentro del contexto latinoamericano - Guevara Bustamente, Andrea (2023)
Romantic love constitutes a repertoire of beliefs about the ideal of love, ideas that build imaginaries about what is expected in relationships, as well as about the behaviors considered appropriate for women and men in the sexual-affective sphere. Violence against women is a recurring crime in Latin America; it is constantly perpetuated within the intimate sphere of the victims, especially by their partners or ex-partners. Taking into account the validity of both phenomena, this research analyzed the influence of the idealization of romantic love on gender violence within couples of heterosexual adolescents and young people in Latin America through a bibliographic review. In this sense, the objective was to analyze the contextualization and impact of this current on gender violence, for which the concept of romantic love and the meaning of gender violence are explained. Furthermore, the work in question showed how the idealization of this theory of Western love has normalized, facilitated and eroticized gender violence within couples, specifically among young people and adolescents in Latin America. In the first instance, the justification of harmful socio-emotional behaviors, such as emotional dependence and the decision to prioritize the partner, was explained based on this socio-historical construction of love. Secondly, the way in which this ideal strengthens gender roles was analyzed. In this way, it was concluded that romantic love facilitates violence, romanticizing aggressive attitudes and gender stereotypes.